Evaluation of the Therapeutic Effect of Lycoramine on Alzheimer’s Disease in Mouse Model - Kiris, Irem; Basar, Merve K.; Sahin, Betul; Gurel, Busra; Coskun, Julide; Mroczek, Tomasz; Baykal, Ahmet Tarik (Current Medicinal Chemistry, 2021)
Background: Alzheimer’s disease is one of the leading health problems characterized by the accumulation of Aβ and hyperphosphorylated tau that account for the senile plaque formations causing extensive cognitive decline. Many of the clinical diagnoses of Alzheimer’s disease are made in the late stages, when the pathological changes have already progressed. Objective: The objective of this study is to evaluate the promising therapeutic effects of a natural compound, lycoramine, which has been shown to have therapeutic potential in several studies and to understand its mechanism of action on the molecular level via differential protein expression analyses. Methods: Lycoramine and galantamine, an FDA approved drug used in the treatment of mild to moderate AD, were administered to 12 month-old 5xFAD mice. Effects of the compounds were investigated by Morris water maze, immunohistochemistry and label- free differential protein expression analyses. Results: Here we demonstrated the reversal of cognitive decline via behavioral testing and the clearance of Aβ plaques. Proteomics analysis provided in-depth information on the statistically significant protein perturbations in the cortex, hippocampus and cerebellum sections to hypothesize the possible clearance mechanisms of the plaque formation and the molecular mechanism of the reversal of cognitive decline in a transgenic mouse model. Bioinformatics analyses showed altered molecular pathways that can be linked with the reversal of cognitive decline observed after lycoramine administration but not with galantamine. Conclusion: Lycoramine shows therapeutic potential to halt and reverse cognitive decline at the late stages of disease progression, and holds great promise for the treatment of Alzheimer’s disease.
Keywords: Lycoramine